Placement of the Internal Pulse Generator for Deep Brain Stimulation in the Upper Back to Prevent Fracture of the Extension Wire Due to Generator Rotation: Case Report. (2010) - Garg, Ankur; Mohan, Avinash L.; Garell, P. Charles
Abstract : Deep brain stimulation (DBS) is a common surgical procedure used for the treatment of Parkinson's disease (PD) and essential tremor. A potential complication of this procedure is hardware failure. The authors report a case of DBS hardware failure in which repeated fractures of the extension wire were caused by abnormal rotational movements of the IPG placed in the loose subclavicular tissue of an overweight female. Implantation of the IPG in the suprascapular area prevented further extension wire fractures. This strategy may be especially relevant in overweight females with loose subclavicular tissue.